Tekstanalyse og tekstproduktion - Helmut Molly (Hermes, 1988)
This paper examines the textuality of two non-authentic "texts" (extracts from graduate level examination papers in written proficiency). The results show that mainly because of defective text-semantic coherence these samples cannot be characterized as texts. It is claimed that a possible explanation of these defects is the heterogeneous ways in which texts are dealt with in foreign language education. Finally there are some remarks about the position of text linguistics.